The Main Problems of SCO Enlargement at the Present Stage - Berdibaevich, S.S.; Kasymovna, Sh.L.; Muratbekovna, S.G.; Tleubaevna, T.B.; Saniyazdanovich, M.K. (Published by Canadian Center of Science and Education, 2015)
Presently the most significant issues of Shanghai Cooperation Organization (SCO) include questions of its further extension, new country-members of SCO team, and what state could be full members of this organization. The issues of SCO extension is actual from 2004-2005 when Mongolia, Pakistan, India and Iran became as observers in SCO. This paper tries to do analysis on countries-observers due to strengthening of these processes when different states, particularly such antagonistic as India and Pakistan, consider their preferences to have partnership with SCO and why SCO accepts these countries. This article is focused on SCO observers’ interests and significance of these countries for SCO itself. Chinese and Russian politics on the new country-observers is also considered in the paper. It is argued that SCO extension perspectives are controversial and they demonstrate that SCO is not ready to increase this organization by including Mongolia, Pakistan, India and Iran to SCO at the present times. Preliminary conclusions are that SCO will not extend in the future and issues of SCO enlargement will not be resolved in upcoming years.
Keywords: Shanghai cooperation organization; international politics; SCO observers; security; regional security; economic partnership; central Asia; South-Eastern Asia